Endoscopic Delivery Method Using a Retrieval Net for Patients with Small-Bowel Capsule Endoscopy Stagnation in the Stomach - Akihiko Sumioka; Shiro Oka; Akiyoshi Tsuboi; Issei Hirata; Sumio Iio; Hidenori Tanaka; Ken Yamashita; Takahiro Kotachi; Ryo Yuge; Yuji Urabe; Shinji Tanaka (Gastroenterology Research and Practice)
With the increasing use of capsule endoscopy (CE), screening tests for the small bowel can be performed with minimal invasiveness. However, occasionally, the entire small bowel cannot be observed because of decreased peristalsis of the stomach. For such cases, we perform delivery of CE by an endoscope. We retrospectively examined the usefulness of the endoscopic delivery method using a retrieval net for patients with CE stagnation in the stomach. From 2,270 patients who underwent small-bowel CE at Hiroshima University Hospital from January 2013 to January 2020, 29 consecutive patients (1.3% of the total number) in whom the small bowel could not be observed due to CE stagnation in the stomach at the time of the initial CE underwent the endoscopic delivery method using a retrieval net for secondary small-bowel CE. This study included 16 male (55%) and 13 female (45%) patients with a mean age of 69.2±13.2 years. 11 patients (38%) had a history of gastrointestinal surgical resection. The entire small bowel could be observed in 19 patients (66%), and CE reached the terminal ileum in the remaining patients. A history of gastrointestinal surgical resection was significantly more frequent in the group where the entire small bowel could not be observed. The rate of small-bowel lesion detection was 55% (16/29). There were no adverse events associated with our endoscopic delivery method. Thus, the endoscopic delivery method using a retrieval net for patients with initial CE stagnation in the stomach may be safe and useful for the detection of small-bowel lesions.